PENGEMBANGAN MEDIA SMART BOX BERBASIS MAKE A MATCH UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SD - Gunawan, Putri Afrinia; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the lack of use of innovative learning media so that it has an impact on low student interest in learning. This research aims to develop a smart box learning media based on make a match to increase students interest in learning IPAS subjects. This research uses a research and development (R&D) method using the ADDIE model which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The results showed that 1) smart box media based on make a match is very feasible to use as evidenced by the results of the experts assessment obtained an average score of 94.21% 2) smart box media based on make a match is practical and interesting to use in learning as evidenced by the results of the teacher and student response assessment by obtaining an average score 93.4% 3) smart box media based on make a match is declared very effective to increase student interest in learning questionnaire assessment obtained a score of 93.5%.